Scaling-up of simultaneous saccharification and fermentation of lactic acid from microwave-alkali-treated empty fruit bunches - Hassan, N. (North Carolina State University, 2017)
The goal of this work was to scale up the simultaneous saccharification and fermentation (SSF) of lactic acid using microwave-alkali-pretreated empty fruit bunches (EFB) from a scale of 16 L to a scale of 150 L. To facilitate the scaling-up process of lactic acid production by Rhizopus oryzae NRRL 395, a scaling-up criterion of constant kLa value was applied. Operating conditions, such as aeration rate and superficial velocity, were varied and evaluated on both scales (16-L and 150-L). The highest lactic acid yield of 6.8 g/L was obtained under an operating condition of 1 vvm (0.061 s-1). Parallel aeration rates were determined for the 150-L fermenter system to obtain the same kLa value as the 16-L fermenter. An operational condition of 0.5 vvm dissolved oxygen supply in the 150-L fermenter was optimal to support an identical value of kLa and production rate of lactic acid for both scales.